Strategi Guru Kelas dalam Menangani Siswa yang Mengalami Kesulitan Belajar Membaca di SD swasta Al-Hidayah - Abdul Fattah Nasution; Nazla Sofi Adinda; Dea Nadhira Mulyadi; Suci Nurhayati (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to describe the strategies used by classroom teachers in addressing students who experience reading difficulties at Al-Hidayah Private Elementary School. Reading difficulties among elementary school students are a common issue and can seriously impact their academic achievement in the future. This research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The findings indicate that reading difficulties are caused by both internal factors, such as a lack of basic phonological skills, and external factors, such as an unsupportive learning environment. To address these challenges, teachers implement adaptive learning strategies, including individual guidance, the use of visual and audio media, and phonetic-based learning approaches. Additionally, collaboration with parents plays an important role in supporting students’ learning processes at home. These strategies significantly help students improve their reading skills and build self-confidence. The study concludes that overcoming reading difficulties requires synergy between teacher strategies, appropriate learning methods, and supportive environments, both at school and at home.